Reversals in Wartime: Alcuin and Charlemagne discuss Retrograde Motion (Interfaces: A Journal of Medieval European Literatures, 2021)
The apparent retrograde motion of the planets was a puzzle for astronomers from the ancient world to the final establishment of heliocentric cosmology in the early modern period, but enjoyed an especially rich discussion in the Carolingian Renaissance. We explore the first stirrings of an eighth-century response to this epistemological challenge in a remarkable series of letters between Alcuin of York and Charlemagne, sent while the latter was on campaign against the Saxons in 798 CE. Their exchange constitutes the longest discussion of the phenomenon of Mars' retrograde motion in the West up to that date. Our consideration of the relevant letters explores Alcuin's ability to marshal diverse and complex explanatory narratives and observational traditions around the problem of the retrograde motion of the planet Mars, even as he was unable to fully reconcile them. Attention to his ultimately unsuccessful (and at times contradictory) attempts at explanation suggest that he relied on knowledge from sources beyond those previously recognized, which we identify. Charlemagne's curiosity about the matter can be located in the much longer context of an ancient tradition of imperial and royal concern with heavenly phenomena; at the same time, the exchange with Alcuin heralds the ninth-century expansion of astronomy away from the computists' preoccupation with the solar and lunar calendrical data required to calculate the date of Easter and towards a more wide-ranging curiosity about observed planetary motion irrelevant to Easter dating and computistical calculations. Alcuin's functional, if not geometrical, assumption of the centrality of the sun in his explanation merits a further examination of the more general sense in which lost ancient heliocentric ideas sustained early medieval echoes.
Keywords: Carolingian Renaissance; Mars' retrograde motion; astronomy; Alcuin of York; Charlemagne